Answer:
-2.7, 1.283, 1.483, 2.263, 3.432 hope this helps
-4y - x - (3y - 9x)...distribute the - thru the parenthesis
-4y - x - 3y + 9x....now combine like terms
8x - 7y <== or -7y + 8x
Answer:
Step-by-step explanation:
x^2 + 2x + 1 = 17
x^2 + 2x = 17 - 1
x^2 + 2x = 16
x^2 + 2x + 1 = 16 + 1
(x + 1)(x + 1) = 17
(x + 1)^2 = 17
x + 1 = sqrt 17
x = -1 (+ - ) sqrt 17
x = -1 + sqrt 17 or x = -1 - sqrt 17 <===
Step-by-step explanation:
2- 7x + 34 - 6-(766)
2-7x + 34 - 6 - 766
2 - 7x - 738
-7x - 736
-(7x + 736